ANALISIS PENERAPAN KOMPETENSI KEPRIBADIAN GURU PAK PADA SISWA KELAS IX SMP NEGERI 1 PORSEA KABUPATEN TOBA SAMOSIR TAHUN PEMBELAJARAN 2017/2018 - Christin Veronika Sinaga (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2018)
Abstract, The purpose of this research is to determine the percentage of personality christian religious education teacher in implementing learning class IX Junior High School 1 Porsea regency Toba Samosir learning year 2017/2018. This research using descriptive quantitative method, population research is 210 people, samples is 42 people. Data were collected by questionnaire covered 40 items based on indicator variables corresponding theory expert and test result validity of the instrument is 37 valid itemsand 3 items not valid. Instrument reliability test result obtained r11 = 0,927 in the category of very high. From data analysis application of the values obtained personality competence Christian Religious Education Teacher in implementing learning = 82,77 % are in the very good category. By t test obtainable thitung = 24,651 ttabel = 1,684, therefore Ho is rejected and Ha accepted.That personalityc christian religious education teacher class Ix Junior High School 1Porsea regency Toba Samosir learning year 2017/2018≥ 61% than expected accepted as true. This research suggests the advanced researcher to examine the influence of personality competence associated with personality